The relationship between knowledge and maternal attitudes in preventing stunting at UPTD Puskesmas Pendopo Inpatient Care - Arlenti, Lety; Putri, Poppy Siska; Habiba, Ayu (Institute of Computer Science (IOCS), 2024)
Background: Stunting is still a serious problem facing Indonesia. Stunting is a condition of growth failure in toddlers due to chronic malnutrition, especially in the first 1,000 days of life. The purpose of this study was to determine the relationship between knowledge and maternal attitudes in preventing stunting at the Pendopo Inpatient Health Center UPTD in 2023. This type of research uses an observational analytical survey method with a cross-sectional design. The population in this study were mothers of toddlers who had children under 2 years old who came to the Pendopo Inpatient Health Center UPTD. The sample in this study was mothers of toddlers who had children under 2 years old who came to the Pendopo Inpatient Health Center UPTD, namely 38 people. The sampling technique used in this study was purposive sampling. Data collection used primary data, processed univariately and bivariately. The results of the univariate analysis Almost half (42.1%) of mothers' knowledge was lacking regarding stunting prevention at the Pendopo Inpatient Health Center UPTD. Most mothers of toddlers with Sufficient Attitudes in Preventing Stunting at the Pendopo Inpatient Health Center UPTD in 2023. The results of the bivariate analysis using the Chi-Square statistical test showed that there was a significant relationship between maternal knowledge and maternal attitudes in Preventing Stunting at the Pendopo Inpatient Health Center in 2023. It is hoped that services can be further improved, through maximum excellent service, holding toddler classes including counseling on stunting, providing additional food for toddlers, and continuing to improve skills, adding more complete facilities and infrastructure for the sake of improving the quality of health services in Indonesia.